Analysis and design of plated structures. - Shanmugam, N. E.; Wang, C. M. (Woodhead Publishing series in civil and structural engineering., 2021)
Analysis and Design of Plated Structures: Stability, Second Edition covers the latest developments in new plate solutions and structural models for plate analysis. Completely revised and updated by its distinguished editors and international team of contributors, this edition also contains new chapters on GBT-based stability analysis and the finite strip and direct strength method (DSM). Other sections comprehensively cover bracing systems, storage tanks under wind loading, the analysis and design of light gauge steel members, applications of high strength steel members, cold-formed steel pallet racks, and the design of curved steel bridges. This is a comprehensive reference for graduate students, researchers and practicing engineers in the fields of civil, structural, aerospace, mechanical, automotive and marine engineering.